Determinan Penggunaan Sistem Informasi Akuntansi Pada UMK di Sleman - Aisy, Hanifah Rihhadatul; Sa’dani, Olivi Sabilla (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The development of micro and small businesses in Sleman plays a role in absorbing labor and supporting regional gross domestic income. Based on this role, it is hoped that micro and small businesses can continue to develop and carry out business in a sustainable manner. In achieving continuous business continuity, the accounting information system is an effort to deal with financial management problems in micro and small businesses. Entrepreneurs have difficulty making decisions when their accounting and information technology knowledge and skills are low. Therefore, this research aims to determine the influence of various aspects of skills and knowledge on the use of accounting information systems in micro and small businesses in Sleman. This research was conducted in Sleman, Special Region of Yogyakarta, the data used was primary data obtained through questionnaires and tested using multiple linear regression analysis. The tool used to carry out this test is SPSS 25 software. The results obtained by the variables of business scale, age of business, level of education and accounting training have a significant positive influence on the use of accounting information systems in MSEs..